Career administration, proactive behavior and career satisfaction: A mediating relationship - Ismail, Azman; Nor, Azmawaty Mohamad; Nowalid, Wan Khairina Mohd; Abdullah, Anis Anisah (Society for Alliance, Fidelity and Advancement (SAFA), 2018)
The need to improve the human aspect has never been found imperative on organizations other than at a time when personnel are challenged daily with efficiency dropping and job performance in low ebb. Hence, it is vital for this study to examine the relationship between career administration, proactive behavior and career satisfaction. A survey method was conducted and 132 self-report questionnaires were collected from employees in a renowned manufacturing firm in the Malaysian petroleum industry. The survey has two significant results: (i) Relationship between job autonomy and proactive behavior has a positive and significant correlation to career satisfaction. (ii) Relationship between transformational leadership and proactive behavior has a positive and significant correlation to career satisfaction. The result posits that proactive behavior is key variable linking career administration to organizational career satisfaction. Implications from this survey and recommendations for future research are made.